Improvement in ARDS experimental model installation: Low mortality rate and maintenance of hemodynamic stability - Haddad, Luciana Branco; Manzano, Roberta Munhoz [UNESP]; Rossi, Felipe de Souza; Freddi, Norberto Antonio; Prado, Cristiane; Rebello, Celso Moura (Elsevier, 2012)
Introduction: Many experimental models using lung lavage have been developed for the study of acute respiratory distress syndrome (ARDS). The original technique has been modified by many authors, resulting in difficulties with reproducibility. There is insufficient detail on the lung injury models used, including hemodynamic stability during animal preparation and drawbacks encountered such as mortality. The authors studied the effects of the pulmonary recruitment and the use of fixed tidal volume (Vt) or fixed inspiratory pressure in the experimental ARDS model installation. Methods: Adult rabbits were submitted to repeated lung lavages with 30ml/kg warm saline until the ARDS definition (PaO 2/FiO 2≤100) was reached. The animals were divided into three groups, according to the technique used for mechanical ventilation: 1) fixed Vt of 10ml/kg; 2) fixed inspiratory pressure (IP) with a tidal volume of 10ml/kg prior to the first lung lavage; and 3) fixed Vt of 10ml/kg with pulmonary recruitment before the first lavage. Results: The use of alveolar recruitment maneuvers, and the use of a fixed Vt or IP between the lung lavages did not change the number of lung lavages necessary to obtain the experimental model of ARDS or the hemodynamic stability of the animals during the procedure. A trend was observed toward an increased mortality rate with the recruitment maneuver and with the use of a fixed IP. Discussion: There were no differences between the three study groups, with no disadvantage in method of lung recruitment, either fixed tidal volume or fixed inspiratory pressure, regarding the number of lung lavages necessary to obtain the ARDS animal model. Furthermore, the three different procedures resulted in good hemodynamic stability of the animals, and low mortality rate. © 2012 Elsevier Inc.
Keywords: Adult respiratory distress syndrome; Animal models; Bronchoalveolar lavage; Tidal volume